Collagenase Clostridium Histolyticum-aaes for Treatment of Cellulite: A Pooled Analysis of Two Phase-3 Trials. Issue 5 (25th May 2022) - Bass, Lawrence S.; Kaufman-Janette, Joely; Joseph, John H.; Kaminer, Michael S.; Clark, James; Fabi, Sabrina G.; Gold, Michael H.; Katz, Bruce E.; Peddy, Kappa; Schlessinger, Joel; Young, V. Leroy; Hurley, David; et al.
Abstract : Background: Collagen-rich fibrous septae and subcutaneous adipose protrusions play a role in cellulite pathophysiology. Collagenase clostridium histolyticum-aaes (CCH-aaes) injection causes enzymatic release of septae to resolve cellulite depressions and create a skin smoothing effect. This analysis pooled data from two identically designed, phase-3, randomized, double-blind, placebo-controlled studies to examine the efficacy and safety of CCH-aaes. Methods: Adult women with moderate/severe cellulite (3–4 on Clinician Reported Photonumeric Cellulite Severity Scale and Patient Reported Photonumeric Cellulite Severity Scale) on the buttocks received up to three treatment sessions (Days 1, 22, and 43) of subcutaneous CCH-aaes 0.84 mg or placebo per treatment area. Composite and individual component response (≥2-level or ≥1-level improvement from baseline in Patient Reported Photonumeric Cellulite Severity Scale and/or Clinician Reported Photonumeric Cellulite Severity Scale) and additional patient-reported outcomes were determined at Day 71. Results: Analysis included 424 CCH-aaes−treated and 419 placebo-treated women. CCH-aaes−treated women were 5.9 times more likely than placebo-treated women to be ≥2-level composite responders at Day 71 (odds ratio [95% confidence interval], 5.9 [2.2–15.4]; P < 0.001). A significantly greater percentage of CCH-aaes−treated women versus placebo-treated women were ≥1-level composite responders at Day 71 (39.4% versus 14.6%; P < 0.001). Subgroup analyses indicated no apparent impact of Fitzpatrick skin type category and baseline cellulite severity (moderate/severe) on CCH-aaes efficacy. An inverse relationship between age and CCH-aaes response was observed in those with a body mass index less than 32 kg per m 2 . The most common adverse events with CCH-aaes were injection-site bruising and injection-site pain. Conclusion: CCH-aaes treatment significantly improved moderate-to-severe buttock cellulite appearance and was generally well tolerated.